10 Granulocyte/monocyte apheresis as maintenance therapy in crohn's disease. (5th April 2017) - Rimmer, P; Donnelly, H; Preedy, H; Makins, R
Abstract : Background: Granulocyte, monocyte apheresis (GMA), extra-corporeal absorptive circuit used to treat acute ulcerative colitis (UC) and Crohn's disease. Use in maintenance therapy following remission is uncertain. Aim: To present the outcomes following treatment of 5 patients with maintenance GMA for Crohn's disease. Method: Notes review of patients. Assessed blood results (full blood count, albumin, c-reactive protein) faecal calprotectin (FC), imaging and subjective patient reporting to determine the response Results: 5 patients (P) were included, of whom: 4 were male, mean age 37.4 (24–57) years. All received previous conventional therapies with no or limited effect or had lost response. All had 8 treatments at weekly intervals as acute therapy followed by maintenance at monthly intervals. P1 (30 year old male, small bowel (SB) Crohn's), 40 columns, consistent normalisation in all markers and FC (from >600 to 248), reversal of temporary colostomy, improvement on MRE, subjective improvement. P 2 (46 year old male, SB Crohn's) 12 columns, consistent improvement in bloods, subjectively in remission. P3 (24 year old male, Crohn's colitis) 9 columns, initial subjective improvement, bloods unchanged from baseline but normal, switched to vedolizumab. P4 (30 year old male, SB Crohn's) 5 columns, no subjective change, stopped. P5 (57 year old female, SB Crohn's) 4 columns, improvement in C-reactive protein, others consistently normal, no change from baseline, subjective improvement but stopped. Conclusions: Five patients received maintenance therapy. Consistent biochemical/subjective symptomatic remission was achieved in two (P1 and 2), subjective remission in a third (P5) but no response in P3 and 4. Remission appeared to continue in those with elevated baseline markers of inflammation. SB Crohn's may respond better than colitis. GMA may have a role as maintenance therapy.